The Effect of Coconut Water on Increasing Biomass Production of Marine Algae (Kappaphycus alvarezii) - Ode, Sri Jafitra Taufik; Tuiyo, Rully; Mulis, Mulis (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
A shortage of seeds and low-quality production of the marine algae Kappaphycus alvarezii are classic problems that farmers encounter. Therefore, growth hormones, a natural ingredient in young coconut water, must be used. This research aimed to analyze the growth rate of the marine algae K.alvarezii using coconut water immersion treatment at different times (0 minutes, 30 minutes, 40 minutes, and 50 minutes) with an initial weight of 50 g. This research was conducted in South Sulawesi, Wakatobi Regency, Wangi-Wangi Selatan District, Liya One Melangka Village from June to October 2023. This research used the RAL method to measure the weight of the marine algae Kappaphycus alvarezii every 10 days and measure water quality for 40 days. The results of the ANOVA analysis in the soaking treatment of K.alvarezii sea algae seeds showed significant effects.